Estoques de carbono e nitrogênio do solo manejado em sistemas de integração - Gregolin, Fernanda Schmitt (2017)
The objective of this study was to evaluate the accumulation of carbon (C) and nitrogen (N), soil density (Ds) and soil microbial biomass carbon (CBM) in an area under three types of cultivation: 1) ILP (Urochloa ruziziensis pasture rotating with maize (Zea mays); 2) ILPF-50 (composed of double row of eucalyptus with 50 m row spacing under maize rotated U.ruziziensis); 3) ILPF-15 (composed of triple row of eucalyptus, with row spacing of 15.0 m, under cultivation of U. ruziziensis in rotation with corn). For comparison purposes, C, N and CBM stock data were obtained from an area of native forest and fallow, located in the vicinity of the experimental area. The analyzes were performed on undeformed (Ds) and deformed soil samples (C / N and CBM contents / stocks), in two 2013 and 2015 evaluation periods. For the evaluation of CBM samples were collected in the 0-10 cm layer, For the contents of C and N stocks were collected in the 0-5, 5-10 and 10-30 cm layers. In relation to Ds, in ILPF-15 and ILPF-50, the influence of the forest component was observed, with the lowest values in the tree lines in relation to the cultivation lines. After four years of implementation of the different integration systems, an average annual increase in C stocks of 1.4 Mg ha-1 in ILPF-50 was obtained; 1.0 Mg ha-1 in ILP and 0.2 Mg ha-1 in ILPF-15. Where the ILPF-50 obtained average C stocks similar to those presented by the native forest in ¼ of the estimated time (20 years). When assessing the horizontal distribution of C and N stocks in the soil, the influence of the forest component was observed, where the highest C and N stock was obtained at 7.5 m (ILPF-15) and at 25.0 m (ILPF -50) away from the eucalyptus lines. In ILPF-50, there was a tendency of increase in C accumulations in the soil, with the increase in N stocks in the soil. In relation to the CBM, the increase in relation to the native forest of 43, 28 and 58% for the ILP treatments was observed; ILPF-50 and ILPF-15 respectively. Concerning the distribution of CBM in the different faces of isolation (north and south) and the different distances of the transect, ILPF-15 and ILPF-50 treatments, the distribution occurred uniformly throughout the treatment, after four years of implementation. Demonstrating the high retention capacity of C and N in integrated systems with crop rotation.